which system of equations can be used to find the roots of the equation 12 x 3-5x=2 x 2+x+6

a. y= 12x3-5x
y=2x2+x+6
b. y=12x3-5x+6
y=2x2+x
c. y=12x3+2x2-4x
y=6
d. y=12x3+2x2-4x+6
y=0

Respuesta :

Answer:

Option (a) is correct.

The system of equation becomes

[tex]y=12x^3-5x\\\\ y=2x^2+x+6[/tex]

Step-by-step explanation:

Given : Equation  [tex]12x^3-5x=2x^2+x+6[/tex]

We have to construct a  system of equations that  can be used to find the roots of the equation [tex]12x^3-5x=2x^2+x+6[/tex]

Consider the given equation [tex]12x^3-5x=2x^2+x+6[/tex]

To construct a system of equation put both sides of the given equation equal to a same variable.

Let the variable be "y", Then the equation [tex]12x^3-5x=2x^2+x+6[/tex]

becomes,

[tex]12x^3-5x=y=2x^2+x+6[/tex]

Thus, The system of equation becomes

[tex]y=12x^3-5x\\\\ y=2x^2+x+6[/tex]

Option (a) is correct.

   

The system of equations are [tex]\boxed{y = 12{x^3} - 5x}{\text{ and }}\boxed{y = 2{x^2} + x + 6}[/tex] that can be used to find the roots of the equation [tex]12{x^3} - 5x = 2{x^2} + x + 6.[/tex] Option (a) is correct.

Further explanation:

Given:

The equation is [tex]12{x^3} - 5x = 2{x^2} + x + 6.[/tex]

The options are as follows,

(a). [tex]y = 12{x^3} - 5x{\text{ and }}y = 2{x^2} + x + 6[/tex]

(b). [tex]y = 12{x^3} - 5x + 6{\text{ and }}y = 2{x^2} + x[/tex]

(c). [tex]y = 12{x^3} + 2{x^2} - 4x{\text{ and }}y = 6[/tex]

(d). [tex]y = 12{x^3} + 2{x^2} - 4x + 6{\text{ and }}y = 0[/tex]

Explanation:

The given equation is [tex]12{x^3} - 5x = 2{x^2} + x + 6.[/tex]

Consider the left hand side of the equation [tex]12{x^3} - 5x = 2{x^2} + x + 6[/tex] as y and the right hand side of the equation [tex]12{x^3} - 5x = 2{x^2} + x + 6[/tex] as y.

[tex]\begin{aligned}y&= 12{x^3} - 5x\\y &= 2{x^2} + x + 6 \\ \end{aligned}[/tex]

The equation matches with option (a). Hence, option (a) is correct.

The system of equations are [tex]\boxed{y = 12{x^3} - 5x}{\text{ and }}\boxed{y = 2{x^2} + x + 6}[/tex] that can be used to find the roots of the equation [tex]12{x^3} - 5x = 2{x^2} + x + 6[/tex]. Option (a) is correct.

Learn more:

  1. Learn more about inverse of the functionhttps://brainly.com/question/1632445.
  2. Learn more about equation of circle brainly.com/question/1506955.
  3. Learn more about range and domain of the function https://brainly.com/question/3412497

Answer details:

Grade: High School

Subject: Mathematics

Chapter: Polynomials

Keywords: polynomial, solution, linear equation, quadratic equation, system of equations, solution of the equations.